Model Problem Based Learning dengan Video Animasi pada Topik Pecahan Di Sekolah Dasar - Dewi, Mentari Sukma; Nuriadin, Ishaq (Universitas Negeri Padang, 2025)
The purpose of this study is to determine the influence of employing animated video learning materials on the learning outcomes for comparable fractions in fourth-grade math students. Research was conducted using a quasi-experimental approach with a control group that only participated in the post-test. This research used a split-class design, with some students as controls and others as experimental subjects. Right from the start, the researchers ensured the instruments were reliable and genuine. In the validity test, researchers used SPSS software, and each of the ten questions was deemed valid. A reliability test value of 0.668 was obtained by using Cronbach's Alpha. The fact that the value is higher than 0.60 indicates that the instrument is regarded as reliable. The hypothesis was tested using the t-test with a significance level (Sig.) of 0.234, which is more than the predetermined threshold of 0.05, using a significance level (α) of 0.05. Beyond that, with a t-count of 5.388 and a t-table of 2.069, the t-count is larger than the t-table. Findings showed that students in classrooms that used animated video learning mediums outperformed those in classes that used more conventional methods.